IDENTIFIKASI KEMAMPUAN MOTOR EDUCABILITY SISWA SEKOLAH DASAR - Rosa Damai Yanti; Eka Supriatna; Rahmat Putra Perdana; Y. Touvan Juni Samodra; Rubiyatno Rubiyatno (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2023)
Abstract: Motor educability is a very important study. The speed at which children learn to move depends on their motor educability. The aim of this study was to describe the motor educability of third grade elementary school students. This research uses a survey method, quantitative descriptive. The research sample was 49 grade 3 elementary school students at SDN Sengawang Tengah, Sambas, West Kalimantan. Measurement of motor educability uses the. IOWA-BRACE TEST motor educability, which consists of 21 test items. The results of the research data were then analyzed using the help of Excel. The data is presented in the form of measures of central tendency. Based on the calculation results obtained status, no student has a very good motor educability status, the overall average ability of motor educability is in the medium category.Key words: Motoric, Motor Educability, Elementary School StudentsAbstrak: motor educability merupakan kajian yang sangat penting. Kecepatan anak untuk belajar gerak tergantung dari kemampuan motor educability. Tujuan penelitian ini adalah untuk mendeskripsikan kemampuan motor educability siswa sekolah dasar kelas III. Penelitian ini menggunakan metode survey, deskriptif kuantitatif. Sampel penelitian berjumlah 49 siswa sekolah dasar kelas 3 SDN Sengawang Tengah, Sambas, Kalimantan Barat. Pengukuran motor educability menggunakan. IOWA-BRACE TEST tes motor educability yang berjumlah 21 item tes. Data hasil penelitian selanjutnya dianalisis dengan menggunakan bantuan exel. Data disajikan dalam bentuk ukuran tendensi sentral. Berdasarkan hasil perhitungan diperoleh status, tidak ada siswa yang memiliki status motor educability yang sangat baik, rerata secara keseluruhan kemampuan motor educability masuk dalam kategori sedang.Kata kunci: Motorik, Motor Educability, Siswa Sekolah Dasar